Pengaruh Likuiditas, Profitabilitas dan Pertumbuhan Penjualan Terhadap Kebijakan Hutang - Ulfah Unnuriyah; Ira Septriana (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
One source of external financing of a company is debt. Therefore, debt-related policies are very important for companies. This study aims to analyze the effect of liquidity, profitability and sales growth on debt policy. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange in 2015 - 2018. The sampling technique used in this study was purposive sampling so that a sample of 39 company data was obtained. The data analysis method used is multiple linear regression analysis. The results of this study indicate that liquidity has a negative and significant effect on debt policy. Meanwhile, profitability and sales growth have no effect on debt policy.